Three phlorotannins from Sargassum carpophyllum are effective against the secretion of allergic mediators from antigen-stimulated rat basophilic leukemia cells. (30th May 2022) - Matsui, Takuya; Ito, Chihiro; Itoigawa, Masataka; Shibata, Toshiyuki
Highlights: Three known phlorotannins were isolated from Sargassum carpophyllum . The phlorotannins suppressed the secretion of allergic mediators in RBL-2H3 cells. The phlorotannins have anti-allergic effects involving the IκB-proteosome pathway. Abstract: Sargassum carpophyllum (Sargassaceae) is a brown seaweed that contains phlorotannins, which are phloroglucinol polymers with reported anti-inflammatory activities. The phlorotannins 2-[2-(3, 5-dihydroxyphenoxy)-3, 5-dihydroxyphenoxy]-1, 3, 5-benzenetriol (1 ), 2, 2′-[[2-(3, 5-dihydroxyphenoxy)-5-hydroxy-1, 3-phenylene]bis(oxy)]bis(1, 3, 5-benzenetriol) (2 ), and 2-[2-[4-[2-(3, 5-dihydroxyphenoxy)-3, 5-dihydroxyphenoxy]-3, 5-dihydroxyphenoxy]-3, 5-dihydroxyphenoxy]-1, 3, 5-benzenetriol (3 ) were isolated from S . carpophyllum . Here, we evaluated the anti-allergic activities of these compounds and comprehensively explored their effects on intracellular protein levels. Immunoglobulin E-sensitized rat basophilic leukemia cells pretreated with any of these three compounds exhibited reduced β -hexosaminidase, prostaglandin D2, and tumor necrosis factor-α secretion compared with dinitrophenyl-human serum albumin (DNP-HSA)-stimulated cells. Reduction of β -hexosaminidase release was dose-dependent but the half-maximal inhibitory concentrations of the compounds were similar (36–51 μM). Proteomics analysis revealed that the three compounds up-regulated 25 proteins and down-regulated 33 proteins compared with DNP-HSA stimulation alone, and slightly suppressed proteasome 5 expression linked to the regulation of IκB. These results demonstrate that these phlorotannins are potentially useful for preventing immediate hypersensitivity. S . carpophyllum may be a functional food.